2008
DOI: 10.2134/agronj2008.0074
|View full text |Cite
|
Sign up to set email alerts
|

Furrow Seeding with Plastic Mulching Increases Stand Establishment and Lint Yield of Cotton in a Saline Field

Abstract: Uniform stand establishment is essential for profi table cotton (Gossypium hirsutum L.) production in saline fi elds. Th is study was conducted during 2003 and 2004 to determine if furrow-bed seeding and plastic mulching improve stand establishment and cotton lint yield in a saline fi eld. Th e experiment was arranged in a split-plot design with seeding patterns (fl at-seeded and furrow-seeded) as main plots and mulching (with or without plastic mulching) as subplots. Th e eff ects of seeding patterns, mulchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 29 publications
4
43
0
Order By: Relevance
“…The results were similar to the split root system, in that both the plant growth and yield were higher with unequal salinity distribution than with equal salinity distribution, because plant roots were able to take up enough water from soil in the low-salinity environment [34]. In the Yellow River Delta of China, Dong et al [49] also found that RF could increase stand establishment and lint yield of cotton in a saline field.…”
Section: Rf Promoted Cotton Growth and Improved Lint Yieldsupporting
confidence: 63%
See 1 more Smart Citation
“…The results were similar to the split root system, in that both the plant growth and yield were higher with unequal salinity distribution than with equal salinity distribution, because plant roots were able to take up enough water from soil in the low-salinity environment [34]. In the Yellow River Delta of China, Dong et al [49] also found that RF could increase stand establishment and lint yield of cotton in a saline field.…”
Section: Rf Promoted Cotton Growth and Improved Lint Yieldsupporting
confidence: 63%
“…Plastic film mulching has proved to be an effective measure to increase soil temperature and to reduce evaporation as well as to prevent salt accumulation [49,50]. However, according to Li et al [51], the temperature under mulch could reach to more than 50 • C at 14:00 during the daytime, and the seedlings might be burned or killed in such a high-temperature environment.…”
Section: Rf Promoted Cotton Growth and Improved Lint Yieldmentioning
confidence: 99%
“…These changes can enhance or reduce the salt effects on physiological responses, and further affect plant growth and development (de Lacerda et al, 2005;Dong et al, 2008). So crop productivity in saline environment depends on not only its tolerance to salt stress but also capacity to recover from salt RESEARCH stress.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic film mulching has been a common agricultural practice since it was introduced to China in 1978 (Dong et al 2009, Zhang et al 2012. Polyethylene (PE) film mulching can conserve soil moisture and raise soil temperature (Dong et al 2008), promote growth and increase yields (Li et al 2004, Dong et al 2009). In peanut production, clear plastic film is the most commonly used, however, higher temperature under the clear mulch during pod development may restrict pod and kernel growth (Reddy et al 1988), and weed control also could be a problem (Waterer 2000), which will reduce the pod yield.…”
mentioning
confidence: 99%